Popular Music and Public Diplomacy : Transnational and Transdisciplinary Perspectives - Dunkel, Mario; Nitzsche, Sina A. (2019)
In the early years of the Cold War, Western nations increasingly adopted strategies of public diplomacy involving popular music. While the diplomatic use of popular music was initially limited to such genres as jazz, the second half of the 20th century saw a growing presence of various popular genres in diplomatic contexts, including rock, punk, reggae, and hip-hop. This volume illuminates the interrelation of popular music and public diplomacy from a transnational and transdisciplinary angle. The contributions argue that, as popular music has been a crucial factor in international relations, its diplomatic use has substantially impacted the global musical landscape of the 20th and 21st centuries.